Code Switching Used by Indonesian Celebrities in Social Media - Hernalia Citra Dewi (Deiksis, 2021)
People who  are capable  of speaking  and  writing two  languages well  arecalled   "bilingual",   they  commonly   switch   a   language   to  another   in   their communication,  that  is  code switching.  This  study  focuses  on  analysing  codeswitching used by  Indonesian Celebrities in Social Media, using theory of code  switching proposed by Romaine  in Susanto (2008)  and Hoffman (1992).The  aims  of  this  research are  1).  to  describe  and  analyzes  the  types  of  codeswitching and 2). To find the most dominant type of them in Social-Media. This study  investigates code switching  used in  Social Media. The  objectives of this  study are  to find out types and  the most dominant  type of  code switching used by Indonesian Celebrities in Social Media. This  study uses  descriptive  qualitative approach.  The  data  are collected from the utterances of Maudy Ayunda and Boy William as Indonesian Celebrities which are analyzed  by using  Romaine  in  Susanto (2008)  and  Hoffman  (1992)  theory oncode switching. It is found that from three videos on social media, 20 data are found and classified into three types of code switching. There are 7 data of inter-sentential of code switching and 12 intra-sentential, and 1 of tag switching. Key words: sociolinguistics, code switching, Social-Media